A facile synthesis of PEGylated Cu2O@SiO2/MnO2 nanocomposite as efficient photo−Fenton−like catalysts for methylene blue treatment - Wu, Mingzhou; He, Shuqing; Ha, Enna; Hu, Junqing; Ruan, Shuangchen (Frontiers in Bioengineering and Biotechnology, 2022)
The removal of toxic organic dyes from wastewater has received much attention from the perspective of environmental protection. Metal oxides see wide use in pollutant degradation due to their chemical stability, low cost, and broader light absorption spectrum. In this work, a Cu2O−centered nanocomposite Cu2O@SiO2/MnO2−PEG with an average diameter of 52 nm was prepared for the first time via a wet chemical route. In addition, highly dispersed MnO2 particles and PEG modification were realized simultaneously in one step, meanwhile, Cu2O was successfully protected under a dense SiO2 shell against oxidation. The obtained Cu2O@SiO2/MnO2−PEG showed excellent and stable photo−Fenton−like catalytic activity, attributed to integration of visible light−responsive Cu2O and H2O2−responsive MnO2. A degradation rate of 92.5% and a rate constant of 0.086 min−1 were obtained for methylene blue (MB) degradation in the presence of H2O2 under visible light for 30 min. Additionally, large amounts of •OH and 1O2 species played active roles in MB degradation. Considering the enhanced degradation of MB, this stable composite provides an efficient catalytic system for the selective removal of organic contaminants in wastewater.